Características realcionadas à compreensão do tratamento entre pacientes iniciando a terapia anti-retroviral no Brasil - Maria das Gracas Braga Ceccato (2008)
Objective: The aim of this study was to evaluate the level of understanding regarding information on medications prescribed among patients initiating anti-retroviral therapy (ARVT), and to determine factors associated with this level of understanding. It is composed of three articles. The first presents a review of the literature on the subject. The second develops a score to determine the level of understanding on ARVT. The third evaluates the factors associated with the level of understanding of this therapy. Methods: For the literature review of published studies on understanding the patient's prescription was the basis searched MEDLINE-PubMed literature. There was cross-sectionalanalysis in which patients of two HIV/AIDS public referral (Belo Horizonte, Brazil) were interviewed after initiating ART. Information on variables related to the characteristics of the patient, the treatment prescribed and the health care professional were collected.The score of patients understanding regarding the medications prescribed was obtained using a latent trait model estimated by the Item Response Theory (IRT), based on the concordance between each patient answer and written prescription. Hierarchical linear regression was used to assesspatients global understanding of ARVT, considering each class of drugs (level 1) and the individual (level 2), also to assess the factors associated with this level of understanding. Results: Of 406 patients evaluated, 37.9% had not reached a minimum level of understanding of the treatment. With a mean age of 35 ± 10 years, most participants were males (56%), afroamerican ethnicity (77%) and had had < 8 years of education (53%). The item with highest level of difficulty was precaution of use. The item dosage was the one which mostly differentiated understanding of ARVT. The model showed 52.25% of the variability of the understanding was explained by the individual. Variables associated (p<0.05) with lowest ART understanding were lower education (< 8 years), lack of knowledge about treatment duration, clinical severity, inadequacy of medical information, little understanding ofpharmacist information, daily number of tablets and ARVT regimen prescribed. Conclusions: The review of studies was enough to justify the importance of the understanding the prescription for the patient and the need to measure the degree of understanding A high proportion of patients with minimum level of ARVT understanding was observed, which can indicate a high potential risk for non-adherence to the therapy. There is a high individual variability in the understanding of information regarding ARVT regimen prescribed. However, there are factors related to the characteristics to the patient (education, clinical severity), to the treatment (daily number of tablets, ARVT regimen prescribed) and tothe healthcare professionals (medical and pharmacist information) associated with the understanding degree. Strategies for reinforcement of information about ARVT should be prioritized among patients with a low level of understanding.